ANALISIS FUNGSI DAN MAKNA PARTIKEL KA DALAM NOVEL KITTO ASHITA WA KARYA YUKIKO EZAKI - Cahyani, Sri (Humanis; Volume 12. No.1. Juli 2015)
Japanese language known as a language contains of various characteristic. One of the unique side of it is the existence of particles also known as ‘joshi’ that plays an important role to build a sentence or even connect a word. There are several types of Japanese particles generally used on daily conversation which is ‘ka’ particle. ‘Ka’ particle is one of the particle mostly used as a question marker. However, it has different function and meaning according to the position it would be. In the other hand, the position of ‘ka’ particle influences both. Therefore, it is important to know what exactly the way to apply them in a sentence theoretically. This research contains of the explanation regarding the use of ‘ka’ particle in a novel with title Kitto Ashita Wa. Related data is collected, classified, and counted according to the differences of each sentence and listed with the proper words. Theory used is A Dictionary of Japanese Particles by Kawashima and Nihon Go No Joshi by Candra. There are various kind of functions and meanings of ‘ka’ particle that can be found as the result of this research. The function of ‘ka’ particles first, is as a word marker to end the sentence by putting it in the middle of it, known as ‘fukujoshi’. Second, is as an interrogative sentence by putting it in the end of it, known as ‘shuujoshi’. The meaning of ‘ka’ particles is to point a certain answer of ‘yes’ or ‘no’, to show a choice of several selections, to be put in the middle of a sentence to show an unclear content of questions, to show an unexplainable intentions, to express a feeling of doubt, to give an approximate number, to be a question marker, to show a beyond expectation’s feeling, to give a rhetorical answer, to give a confirmation, to show an unclear meaning of a statement, and to ask someone doing something
Keywords: ka, particle, function, meaning